How Canadians Communicate IV: Media and Politics - Waddell, Christopher (Athabasca University Press, 2012)
Substantial changes have occurred in the nature of political discourse over the past thirty years. Once, traditional media dominated the political landscape, but in recent years Facebook, Twitter, blogs and Blackberrys have emerged as important tools and platforms for political campaigns. While the Canadian party system has proved surprisingly resilient, the rhythms of political life are now very different. A never-ending 24-hour news cycle has resulted in a never-ending political campaign. The implications of this new political style and its impact on political discourse are issues vigorously debated in this new volume of How Canadians Communicate, as is the question on every politician?s mind: How can we draw a generation of digital natives into the current political dialogue? With contributions from such diverse figures as Elly Alboim, Richard Davis, Tom Flanagan, David Marshall, and Roger Epp, How Canadians Communicate IV is the most comprehensive review of political communication in Canada in over three decades ? one that poses questions fundamental to the quality of public life.